Geography and the Political Imaginary in the Novels of Toni Morrison - Beavers, Herman (Geocriticism and Spatial Literary Studies, 2018)
This book examines Toni Morrison's fiction as a sustained effort to challenge the dominant narratives produced in the white supremacist political imaginary and conceptualize a more inclusive political imaginary in which black bodies are valued. Herman Beavers closely examines politics of scale and contentious politics in order to discern Morrison's larger intent of revealing the deep structure of power relations in black communities that will enable them to fashion counterhegemonic projects. The volume explores how Morrison stages her ruminations on the political imaginary in neighborhoods or small towns; rooms, houses or streets. Beavers argues that these spatial and domestic geographies are sites where the management of traumatic injury is integral to establishing a sense of place, proposing these "tight spaces" as sites where narratives are produced and contested; sites of inscription and erasure, utterance and silence. .